大陸地區課程發展機制的結構層次與關係The Structural Hierarchy and Relations of the Curriculum Development Mechanism in Chinese Mainland - 吳剛平Gang-Ping Wu; 韓輝Hui Han (Higher Education Foundation, 2011)
中央集權機制、地方分權機制與學校自主機制是課程發展機制的三種基本型 態。在大陸地區，儘管在管理體制上基礎教育主要由地方負責，但在課程發展方面 卻是典型的中央集權機制，實行的是統一的國家課程發展策略，並且通過自上而下 的行政推動來實施。 大陸地區在統一的國家課程框架下，課程發展機制呈現出明顯的層次性結構特 徵，不同層次間存在著主導、輔助、強化、補償、監督及調適等多重作用和複雜關 係，共同影響著課程發展機制系統的運行走向和功能效應。 由於統一的國家課程難以適應不同地區、學校和學生的差異性，所以國家課程 框架也試圖經由地方和校本課程發展策略實現對於國家課程的調節及補充和拓展功 能。然而，集權機制下的地方和校本課程發展卻並不如其政策所預期的那樣順利， 特別是在體制與觀念、管理與評價，以及現實需要與文化傳統之間存在內在的矛盾 和衝突，導致集權機制下的地方和校本課程發展與分權機制下的地方和校本課程發 展存在著不同的意義理解和策略選擇。 There are three basic forms of curriculum development mechanism, which are centralization, decentralization and school autonomation. In Chinese Mainland, basic education is the responsibility of local authorities according to the management system, but its curriculum development mechanism is a typical form of centralization with a uniform strategy of national curriculum development. Under the national curriculum frameworks, its curriculum development mechanism shows a distinct structural hierarchy in which there are complex relations and coactions of dominance, assistance, reinforce, compensation, supervision and adjustment. The curriculum developers under the mechanism of centralization are trying to fi nd a way of decentralization to counteract the centralization's weakness. One of their strategies is local and school-based curriculum development (SBCD), as has occurred in Chinese Mainland. But in fact, SBCD under the mechanism of centralization doesn't go on as smoothly as its policy makers expect. Especially there are many internal contradictions between and within institutions and ideas, managements and evaluations, current needs and cultural traditions. Therefore, the mechanism of centralization has brought about greatly different meaning understanding and strategy making in SBCD from the mechanism of decentralization.